2020
DOI: 10.1038/s41438-020-00402-0
|View full text |Cite
|
Sign up to set email alerts
|

The loss of function of HEL, which encodes a cellulose synthase interactive protein, causes helical and vine-like growth of tomato

Abstract: Helical growth is an economical way for plant to obtain resources. The classic microtubule–microfibril alignment model of Arabidopsis helical growth involves restriction of the appropriate orientation of cellulose microfibrils appropriately in the cell walls. However, the molecular mechanism underlying tomato helical growth remains unknown. Here, we identified a spontaneous tomato helical (hel) mutant with right-handed helical cotyledons and petals but left-handed helical stems and true leaves. Genetic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
6
2
Order By: Relevance
“…Although CSI1 could have other functions than guidance, our work suggests that CSI1 contributes to growth coordination by translating cell polarity into growth direction, through CESA guidance by microtubules. Whereas we did not observe any twisting phenotype in sepal, csi1 mutation leads to twisting of other organs such as the leaf 49,50 , hypocotyl or shoot 51 . Instead, csi1 sepal featured snakey cells.…”
Section: Discussioncontrasting
confidence: 93%
“…Although CSI1 could have other functions than guidance, our work suggests that CSI1 contributes to growth coordination by translating cell polarity into growth direction, through CESA guidance by microtubules. Whereas we did not observe any twisting phenotype in sepal, csi1 mutation leads to twisting of other organs such as the leaf 49,50 , hypocotyl or shoot 51 . Instead, csi1 sepal featured snakey cells.…”
Section: Discussioncontrasting
confidence: 93%
“…The study found that the two dwarf Trifolium varieties were controlled by one and two recessive genes, respectively. Recessive genes also control the lefthanded helix of tomato stems (Yang et al, 2020). However, Lin et al (2007) studies the phenotypic statistics of the progenies obtained from a cross of twisty Salix matsudana with wild-type plants and concluded that the twisty phenotype is controlled by a dominant gene.…”
Section: Inheritance Of Trunk Twistingmentioning
confidence: 99%
“…Thus, these vine-like tomato plants with compact and early yielding characteristics (Kwon et al 2020 ) can be developed to accommodate the plant size and space restrictions of urban agriculture. Recently, the CRISPR/Cas9-mediated mutation of the tomato HEL gene identified in a spontaneous tomato helical ( hel ) mutant also caused vine-like growth of tomato (Yang et al 2020 ), which provides a new idea for developing urban agriculture in the future.…”
Section: Applications Of Genome Editing In Tomato Improvementmentioning
confidence: 99%